Biotin-functionalized targeted polydiacetylene micelles. Issue 29 (26th March 2018) - Doerflinger, Anaëlle; Quang, Nam Nguyen; Gravel, Edmond; Pinna, Guillaume; Vandamme, Marie; Ducongé, Frédéric; Doris, Eric
Abstract : Polydiacetylene micelles were functionalized with controlled amounts of biotin using bioorthogonal click chemistry. Abstract : Polydiacetylene micelles were functionalized with controlled amounts of biotin using bioorthogonal click chemistry. The biotinylated micelles were evaluated in the selective targeting of the MCF-7 cancerous cell line and were shown to be readily internalized. The efficiency of the cellular uptake was correlated to the density of grafted biotin.